2024
DOI: 10.1098/rspb.2023.2253
|View full text |Cite
|
Sign up to set email alerts
|

Cool-edge populations of the kelp Ecklonia radiata under global ocean change scenarios: strong sensitivity to ocean warming but little effect of ocean acidification

Damon Britton,
Cayne Layton,
Craig N. Mundy
et al.

Abstract: Kelp forests are threatened by ocean warming, yet effects of co-occurring drivers such as CO 2 are rarely considered when predicting their performance in the future. In Australia, the kelp Ecklonia radiata forms extensive forests across seawater temperatures of approximately 7–26°C. Cool-edge populations are typically considered more thermally tolerant than their warm-edge counterparts but this ignores the possibility of local adaptation. Moreover, it is unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Changes in trait-temperature relationships due to thermal adaptation in natural populations are expected in response to climate warming (Angilletta 2009), and previous studies have shown that local adaptation in physiological traits can facilitate different thermal optima among populations (e.g., Atlantic cod (Righton et al 2010), kelp (Britton et al 2024), corals (Howells et al 2013) and invertebrates (Sanford and Kelly 2011)). However, adaptive capacities and the pace of thermal adaptation differ among species (Martin et al 2023) and depend on life-history trade-offs, underlying genetic variation, the potential for gene flow (Kirkpatrick and Barton 1997), and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in trait-temperature relationships due to thermal adaptation in natural populations are expected in response to climate warming (Angilletta 2009), and previous studies have shown that local adaptation in physiological traits can facilitate different thermal optima among populations (e.g., Atlantic cod (Righton et al 2010), kelp (Britton et al 2024), corals (Howells et al 2013) and invertebrates (Sanford and Kelly 2011)). However, adaptive capacities and the pace of thermal adaptation differ among species (Martin et al 2023) and depend on life-history trade-offs, underlying genetic variation, the potential for gene flow (Kirkpatrick and Barton 1997), and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…That is, to what extent populations conform to a global, species-wide thermal performance curve, versus having developed local thermal response curves with local temperature optima in order to have higher fitness in their local habitats. In other taxa, such as kelp (Britton et al 2024), corals (Howells et al 2013), invertebrates (Sanford and Kelly 2011), and phytoplankton (Thomas et al 2012), there is a growing evidence that local adaptation has lead to populations exhibiting different responses in growth (individual or population) to ocean warming. However, studies on fishes are scarcer (but see Neuheimer and Grønkjaer (2012) and Beaudry-Sylvestre et al…”
Section: Introductionmentioning
confidence: 99%